Effectiveness of Highly Active Anti-retroviral Therapy (HAART) in the Adult Population in the Ashanti Region of Ghana - Kwaku G. Oppong; Eric Boakye-Gyasi; Kwesi B. Mensah; Ralph Obeng; Akua A. Abruquah; Eric Woode (Universitas Padjadjaran, Indonesia, 2021)
AIDS is the late stage of infection with the Human Immunodeficiency Virus (HIV). Even though the Highly Active Antiretroviral Therapy (HAART) for the management of HIV/ AIDS has been in existence in Ghana since 2003, there is still limited data on their effectiveness. This study therefore sort to ascertain the effectiveness of HAART used at Anti-retroviral therapy (ART) Centres in the Ashanti region of Ghana by assessing its effects on immunological and haematological markers as well as some significant indicators such as body temperature and blood pressure changes. The study was a retrospective cross sectional study which reviewed medical record folders of 156 HIV infected patients who had attended the selected ART centres in the Ashanti region of Ghana between 2010 and 2014. About 49% of the study population had a significant rise in their CD4 counts after six months strict adherence to specific HAART regimen. HAART effectively reduced viral loads and increased CD4 counts in most of the patients whose medical record folders were reviewed. Socioeconomic factors, formal education and lack of health literacy had a significant effect on adherence to the HAART regimen, however; marital status of patients did not have any significant effect on adherence, CD4 counts and the haemoglobin concentration of patients. Based on results obtained from this study, HAART could be considered as effective in the adult population in the Ashanti region of Ghana provided there is a high level of adherence. Immunological and haematological markers for the assessment of effectiveness could also improve with high adherence recommended HAART regimen